Literature Review: Dampak Kurang Tidur Terhadap Working Memory Pada Anak dan Remaja - Jessica Leatemia; Rimawati Tedjasukmana; Susilo Susilo (Fakultas Kedokteran dan Ilmu Kesehatan Ukrida, 2023)
One of the most important causes of disruption in a person’s quality of life is a lack of sleep. Children and adolescents need about 9 hours of sleep every night. The researchers said that sleep is vital for brain development, nerve plasticity, and memory consolidation in children and adolescents. Various surveys have investigated the impact of lack of sleep on learning and memory in children and adolescents, and there is growing evidence that disturbed sleep has a negative impact on the process of learning and memory. Shorter sleep durations are associated with lower working memory performance. This literature review used the method of searching for articles in databases such as Google Scholar, PubMed, Fronties, Emerald, and Proquest. We found 42 journals but of 10 that met the inclusion criteria of this research. The results show that children and adolescents who experienced insufficient sleep have decreased working memory, attention, and increased drowsiness, which can interfere with school learning activities and lead to a decline in academic performance. Lack of sleep also leads to changes in brain network connectivity associated with decreased working memory performance.